A case in Europe of feline histoplasmosis apparently limited to the skin. Issue 6 (9th October 2013) - Fischer, Nina M.; Favrot, Claude; Monod, Michel; Grest, Paula; Rech, Katia; Wilhelm, Sylvia
<x xml:space="preserve">Abstract</x> Background – Histoplasma capsulatum has a worldwide distribution, but reports in Europe remain rare. We present the second report of histoplasmosis in a cat in Europe and, to the best of our knowledge, the first case of feline histoplasmosis infection apparently limited to the skin. Conclusions and clinical importance – Histoplasmosis should be included in the differential diagnosis of nodular diseases of cats worldwide. <boxed-text content-type="graphic" id="vde12077-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>